Exploitation of viral properties for intracellular delivery‡. (30th May 2014) - Galdiero, Stefania; Falanga, Annarita; Vitiello, Mariateresa; Grieco, Paolo; Caraglia, Michele; Morelli, Giancarlo; Galdiero, Massimiliano; Morelli, Giancarlo; Toniolo, Claudio; Venanzi, Mariano
<x xml:space="preserve">Abstract</x> Nanotechnology is an expanding area of study with potentially pivotal applications in a discipline as medicine where new biomedical active molecules or strategies are continuously developing. One of the principal drawbacks for the application of new therapies is the difficulty to cross membranes that represent the main physiological barrier in our body and in all living cells. Membranes are selectively permeable and allow the selective internalization of substances; generally, they form a highly impermeable barrier to most polar and charged molecules, and represent an obstacle for drug delivery, limiting absorption to specific routes and mechanisms. Viruses provide attracting suggestions for the development of targeted drug carriers as they have evolved naturally to deliver their genomes to host cells with high fidelity. A detailed understanding of virus structure and their mechanisms of entry into mammalian cells will facilitate the development and analysis of virus‐based materials for medical applications. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.